Paracellular transport: opening the gates for growth - Riechmann, Veit (Developmental cell, 2021)
Epithelial barriers can open their junctions to enhance paracellular flux. A new article by Isasti-Sanchez et al. in this issue of Developmental Cell shows how changes in cell adhesion and relaxation of acto-myosin tension cooperate in opening the cell vertices of the Drosophila follicular epithelium.